2022
DOI: 10.1097/corr.0000000000002494
|View full text |Cite
|
Sign up to set email alerts
|

Does Addressing Mental Health During a Musculoskeletal Specialty Care Visit Affect Patient-rated Clinician Empathy?

Abstract: BackgroundUnhelpful thoughts and feelings of worry or despair about symptoms account for a notable amount of the variation in musculoskeletal symptom intensity. Specialists may be best positioned to diagnose these treatable aspects of musculoskeletal illness. Musculoskeletal specialists might be concerned that addressing mental health could offend the patient, and avoidance might delay mental health diagnosis and treatment. Evidence that conversations about mental health are not associated with diminished pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Sixth, the recorded encounters include initial and follow-up visits. Although one might expect more empathetic opportunities at initial visits, prior research has demonstrated no such association, so in this study, we included both new and return visits [34,36,48,75].…”
Section: Limitationsmentioning
confidence: 99%
“…Sixth, the recorded encounters include initial and follow-up visits. Although one might expect more empathetic opportunities at initial visits, prior research has demonstrated no such association, so in this study, we included both new and return visits [34,36,48,75].…”
Section: Limitationsmentioning
confidence: 99%
“…In this symposium, you will find evidence that shows how communication effectiveness during patient encounters is not correlated with patient ratings [3]. You will see how surgeons can be trained to identify unhelpful thinking and feelings of distress in their patients [2], and how noticing these aspects of illness does not, on average, harm the relationship [6]. Combined, these papers force us to rethink how we incorporate evaluation and treatment of mental health in musculoskeletal specialty care.…”
mentioning
confidence: 99%